BSCIC'S industrial estate programme an assessment - Chowdhury, Nuimuddin, 1948- (Dhaka, Bangladesh : Bangladesh Institute of Development Studies, 1987)
Study of a program initiated by Bangladesh Small & Cottage Industries Corporation.
Master microform held by: DLC.
Bibliography: p. [52]
Microfiche.
Keywords: Industrial districts -- Bangladesh; Small business -- Bangladesh